Pengaruh Pengelolaan Modal Kerja dan Struktur Modal terhadap Profitabilitas pada Perusahaan Kosmetik dan Perawatan Tubuh yang Terdaftar di BEI Tahun 2020-2024 - Astika Jabir; M.Ikhwan Maulana Haeruddin; Annisa Paramaswary Aslam; Anwar, Anwar; Nurman, Nurman (Universitas 45 Surabaya, 2026)
This study aims to analyze the influence of working capital management and capital structure on profitability in cosmetic and personal care manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the period 2020–2024. This research employs a quantitative approach using multiple panel data regression, in which the data utilized are secondary data obtained from the annual financial statements of six companies during the study period. The independent variables consist of working capital management proxied by the Current Ratio (CR) and capital structure proxied by the Debt to Equity Ratio (DER), while the dependent variable is profitability measured using Return on Assets (ROA). The results indicate that working capital management has an insignificant effect on profitability, whereas capital structure has a positive and significant effect on profitability. Simultaneously, both independent variables significantly influence profitability, suggesting that capital structure plays a more dominant role compared to working capital management in increasing the company’s ability to generate profits during the observed period.